Usage Policy-Based CPU Sharing in Virtual Organizations - Dumitrescu, Catalin; Foster, Ian (Fifth IEEE/ACM International Workshop on Grid Computing, 2004)
Resource sharing within Grid collaborations usually implies specific sharing mechanisms at participating sites. Challenging policy issues can arise within virtual organizations (VOs) that integrate participants and resources spanning multiple physical institutions. Resource owners may wish to grant to one or more VOs the right to use certain resources subject to local policy and service level agreements, and each VO may then wish to use those resources subject to VO policy. Thus, we must address the question of what usage policies (UPs) should be considered for resource sharing in VOs. As a first step in addressing this question, we develop and evaluate different UP scenarios within a specialized context that mimics scientific Grids within which the resources to be shared are computers. We also present a UP architecture and define roles and functions for scheduling resources in such grid environments while satisfying resource owner policies.